Epigenetic silencing of DLEC1 correlates with tumor immune microenvironment and predicts immunotherapy prognosis in multiple cancers - Ruijie Ming; Qi Xiong; Shuh-Ying Tan; Lili Li; Shujie Bao; Jianhua Wang; Lijuan Zhao; Xiaoqian He; Zeze Zheng; Yan Wang; Xiaoyu Liu; Jun Tang; et al. (Human Genetics, 2026)
Cancer remains a major health issue globally, with increasing incidence and mortality rates. While immunotherapy has revolutionized cancer treatment, not all patients benefit, urging the identification of predictive biomarkers. This study utilized public datasets and tumor samples to examine the expression and promoter hypermethylation of DLEC1 in normal and tumor tissues, to evaluate its potential as prognostic and immunotherapy marker. In vitro and in vivo experiments on breast cancer (BrCa) cell lines were conducted to explore the functions and mechanisms of DLEC1 . The prognostic significance of DLEC1 downregulation and its impact on immune cell infiltration and immunotherapy efficacy were analyzed using the GEO and TCGA databases. DLEC1 was frequently downregulated and methylated across multiple cancers. In BrCa, expression of DLEC1 inhibited tumor cell proliferation, induced apoptosis, and activated the interferon lambda1 signaling pathway, indicating its important role as a bona fide tumor suppressor and immunoregulator. High DLEC1 expression correlated with better prognosis in several cancer types and with increased immune cell infiltration. Cancer patients with high DLEC1 expression showed improved overall and progression-free survival under immune checkpoint inhibitor therapies, such as anti-CTLA4, anti-PD1 and anti-PDL1. DLEC1 promoter hypermethylation is a promising biomarker for cancer prognosis and potential immunotherapy response prediction. Its expression and promoter hypermethylation status could thus help to guide clinical treatment strategies for cancer patients, particularly of breast cancer.

Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Plastic fragments impair soil organic carbon persistence through reshaping microbial metabolism and decreasing plant carbon supply in dryland ecosystems - Meng-Ying Li; Wei Wang; Yudi M. Lozano; Jia-Yao Yang; Yue Ma; Xiao-Bin Xiong; Shuang-Jin Huang; Muhammad Ashraf; Jian-Ming Li; Yun-Li Xiao; Zheng-Guo Cheng; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

AM fungal and rhizobacteria jointly enhance vegetable waste decomposition in soils and harvest environmental and agronomic benefits in dryland - Muhammad Maqsood Ur Rehman; Sidra Khattak; Ling Zhao; Yun-Li Xiao; Ying Zhu; Awais Iqbal; Rafi Ullah; Nang Chang; Muhammad Abrar; Jian-Ming Li; Hao Sun; Adnan Khan; et al. (Agriculture, Ecosystems & Environment, 2026)

Fe-Co/sodalite derived from coal gangue via in-situ Fe utilization for synergistic peroxymonosulfate activation: Degradation of sulfamethoxazole, pathway elucidation, and toxicity attenuation - Yiwen Li; Huangsiyu Zhao; Jiang Yu; Pengxinyue Huang; Ming Chen; Yinying Jiang; Jingyi Xiong; Jinchao Huang; Hongbin Jiang (Journal of Water Process Engineering, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Investigations on ballistic behaviour of additive manufactured 316L stainless steel corrugated sandwich panels filled with ultra-high performance geopolymer concrete - Jian Liu; Cunyi Li; Guobin Li; Sihao Lin; Ming-Xiang Xiong; Jianguang Fang (Engineering Structures, 2026)

Chemical constituents from Micromeria biflora and their chemotaxonomic significance - Chen Peng; Xing-Li Zhang; Deng-Li Xiong; Fei-Yan Zhao; Kun Xie; Hong-Ping He; Ming-Ming Li (Biochemical Systematics and Ecology, 2026)

Isodonoids A–L: Ent-kauranoid diterpenoid-flavanone conjugates from Isodon rubescens - Can-Can Wang; Meng-Yu Bao; Hui-Ying Li; Hao-Ming Xiong; Kei-Fong Ng; Li-Ping Bai; Wei Zhang; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

OsSultr1;1 and OsZIP4 mediate cadmium uptake and transport in rice: evidence from high and low Cd-accumulators - Xin Qu; Chen He; Bingcai Xiong; Changfu Wu; Haoran Li; Xiaoyan Song; Shufeng Wang; Hongxia Du; Ming Ma (Journal of Hazardous Materials, 2026)

Reaction engineering of a solar chimney-driven honeycomb photocatalytic reactor for outdoor low concentration methane oxidation - Hanbing Xiong; Tingzhen Ming; Yongjia Wu; Liwen Mu; Renaud de Richter; Wenting Lin; Wenyu Li; Chong Peng; Wei Li (Chemical Engineering Journal, 2026)

Transformation of waste cotton fibers into pore-adjustable photothermal aerogels for improved salt tolerance and enhanced desalination performance - Xin Zhong; Jiaqi Fu; Yuhang Yu; Shengjie Zheng; Weiming Wang; Jun Xiong; Ming Li (Chemical Engineering Journal, 2026)

A simultaneous in-situ growth strategy to prepare CdS@SnO2 composites possessing high-density heterointerfaces for efficient U(VI) reduction - Zihui Wang; Ji-Ming Yu; Longfei Zhai; Haohao Li; Mengna Yan; Xi Feng; Rongfang Xu; Juan Ma; Wei-Wei Xiong (Chemical Engineering Journal, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Unexpected V-shaped temperature dependence of methane fluxes informing its sources in a megacity of China - Ruilin Zhang; Yibo Huangfu; Bin Yuan; Xiaoxiao Zhang; Xianjun He; Thomas Karl; Yang Ding; Hongjuan Li; Kyung-Eun Min; Ying Xiong; Xiao-Bing Li; Zhe Peng; et al. (Science Bulletin, 2026)

Dredging changes the controls, pathways and environmental sensitivity of N2O emissions in shallow lakes - Rongwei Xiong; Yong Li; Ming Chen; Zhiyang Zhou; Zhengliang Jiang; Xichen Che (Journal of Environmental Management, 2026)

Revealing phenological vulnerabilities in wheat yield formation under climate warming: a process-based framework for adaptive breeding - Ming Li; Shizhao Li; Xiaoli Wu; Ling Wu; Miao Liu; Tao Xiong; Chaosu Li; Yonglu Tang (Agricultural and Forest Meteorology, 2026)

A novel method of determining optimal GNSS station density for NWP - Qingzhi Zhao; Qingfang Chen; Yongjie Ma; Haojie Li; Anbang Wu; Ming Liu; Yibin Yao; Hong Liang; Hongwu Guo; Yuxing Zhao; Jing Yang; Qingyuan Guo; et al. (Advances in Space Research, 2026)

A GNSS ZTD enhancement framework integrating physical constraints and hybrid neural networks - Haojie Li; Qingzhi Zhao; Hongwu Guo; Anbang Wu; Ming Liu; Yibin Yao; Zhaoliang Zeng; Hong Liang; Qingyuan Guo; Yongjie Ma; Jiasong Tian; Zhaohui Xiong (Advances in Space Research, 2026)

Sulfur and copper isotope fractionation during planetesimal collisions: Insights from shock metamorphism in ordinary chondrites - Ming-Yang Li; Dan Zhu; De-Liang Wang; Shi-Jie Li; Xiong-Yao Li; Jian-Zhong Liu; Ying-Kui Xu (Acta Geochimica, 2026)

Seismic behavior of concrete shear walls fully reinforced with GFRP bars: Effects of shear span ratio and boundary elements - Ming-Xiang Xiong; Yan-Di Yang; Zhi-Zhao Li (Soil Dynamics and Earthquake Engineering, 2026)

Systematic characterization of FBP gene family in Saccharum reveals ScFBP3 as a key regulator of sucrose-mediated plant branching - Huiwen Zhou; Hanmin Luo; Minyi Wei; Ting Luo; Faqian Xiong; Ming Li; Lihang Qiu; Haifeng Yan (Plant Science, 2026)

Cattail leaf-based photothermal aerogel for all-day freshwater production powered by solar energy and Joule heating - Jiaqi Fu; Jing Wu; Ziqi Liu; Shengjie Zheng; Yuming Wu; Jun Xiong; Ming Li (Desalination, 2026)

Real-time identification of natural ventilation pathways in high-rise housing using distributed PVA sensing and graph-based flow network model - Shilin Ming; Jianwei Li; Shengyu Liu; Hongxin Tian; Yuzhen Zhang; Chenyang Qin; Min Wang; Xiong Shen (Building and Environment, 2026)

Genetic effects on feeding habits: An integrated analysis of intestinal histomorphology, digestive enzyme activities, and multi-omics in hybrids from Micropterus salmoides ♀ × Lepomis cyanellus ♂ - Haitao Zhong; Chiye Zhao; Chaoying Luo; Zheduo Xiong; Yan Li; Hong Chen; Mingli Liu; Yilin Wu; Yuheng Wang; Chun Zhang; Chang Wu; Qizhi Liu; et al. (Aquaculture, 2026)

Experimental investigation on low-temperature performance of the CO2 indirect heat pump integrated system with air and waste heat sources for electric vehicles - Haixu Teng; Ming Li; Shuangyuan Xiong; Zhikun Liu; Chunhong Lu; Xinyue Feng; Haikang Chen; Wei Chang; Yan Jiang (International Journal of Refrigeration, 2026)

Atomic condensation of Na and K vapor followed by oxidation in lunar impact glass beads revealed by Chang’E-6 - Ming-Yang Li; Ying-Kui Xu; Dan Zhu; De-Liang Wang; Yi-Cao Zhou; Bing Mo; Shi-Jie Li; Yang Li; Xiong-Yao Li; Jian-Zhong Liu; Wei Du; Yun Liu (Earth and Planetary Science Letters, 2026)

ExpertCast: a framework for short-term rainfall forecasting integrating knowledge-enhanced learning and neural networks - Haojie Li; Qingzhi Zhao; Yibin Yao; Hong Liang; Zhaoliang Zeng; Hongwu Guo; Anbang Wu; Ming Liu; Jinchao Bai; Yuxing Zhao; Yongjie Ma; Jing Yang; et al. (Advances in Space Research, 2026)

Experimental study on dual-heat-source collaborative optimization of vehicle CO2 thermal management system using integrated multi-strategy closed-loop algorithm - Haixu Teng; Ming Li; Yulong Li; Han Su; Shuangyuan Xiong; Chunhong Lu; Xinyue Feng; Yan Jiang (International Journal of Refrigeration, 2026)

Research on an intelligent precise aeration control system for wastewater treatment based on LSTM models - Qunli Li; Kai Wang; Genevieve Faith Horace; Peiting Jiang; Yanyan Xiong; Fujian Huang; Yong Wang; Wenlai Xu; Ming Zhong (Journal of Water Process Engineering, 2026)

Palladium recovery from wastewater using electric field-enhanced ultrafiltration assisted with polyethyleneimine and electro-decomplexation/electrodeposition - Hang Yin; Wenwu Li; Shuhuai Shen; Saina Zheng; Dafang Fu; Jianglei Xiong; Ming Chen (Journal of Cleaner Production, 2026)

Shear response and economic efficiency of steel reinforced ECC hollow beam without web reinforcement: Towards lightweight structure development - Qiao Liao; Zi-Ming Tang; Bi-Xiong Li; Feng Dai; Ke-Quan Yu (Engineering Structures, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

Lacticaseibacillus rhamnosus LGG Suppresses Osteoclastogenesis via TLR6/NF-κB Modulation and Attenuates Ovariectomy-Induced Bone Loss in Mice - Kangjun Xiong; Jianghua Li; Yaqing Liu; Yang Pan; Yiping Huang; Dongdong Zhan; Lutong Zhang; Ming Tang; Jing Li; Haohao Sun (Probiotics and Antimicrobial Proteins, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Enhancing climate resilience of global dryland maize to cope with future 50-year climate warming - Jing Wang; Bao-Zhong Wang; Fei Mo; Yinglong Chen; Mohammad Ashraf; Yang Wang; Jian-Ming Li; Hai-Xia Duan; Yajie Song; Levis Kavagi; Hong-Yan Tao; You-Cai Xiong (Global Environmental Change, 2026)

Key structural characteristics enhancing digestion resistance in rice starch-sugarcane polyphenols complexes - Zhang Tong; Li Jia-Jiong; Fu Xiong; Wang Ping-Ping; Chen Hai-Ming; Chen Chun (Food Chemistry, 2026)

Cereal-legume intercropping stabilizes yield and economic advantages under variable rainfall in semiarid rainfed environment - Wei Wang; Bao-Zhong Wang; Wei Zhang; Meng-Ying Li; Jian-Ming Li; Sheng-Jun Ji; Muhammad Abrar; Muhammad Maqsood Ur Rehman; Wasim Khan; Hong-Yan Tao; Mohamed S. Sheteiwy; Wen-Ying Wang; et al. (European Journal of Agronomy, 2026)

Intelligent nanofiber membrane with humidity sensing and thermoregulation dual functions - Weibing Zhong; Yue Li; Xin Chen; Yanyan Li; Xincheng Ding; Yi Xiong; Mufang Li; Xiaojuan Ming; Jing Lu; Dong Wang (Chemical Engineering Journal, 2026)

Oligosaccharide mapping analysis through UPLC-Orbitrap-HRMS and enzymatic hydrolysis from Polygonatum odoratum (Mill.) Druce - Qing-Hua Liu; Liu Yang; Yue Wang; Hao-Ming Xiong; Cai-Yun Wang; Guo-Yuan Zhu; Li-ping Bai; Zhi-Hong Jiang; Wei Zhang (Carbohydrate Polymers, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Understanding the role of C5a/C5aR1-mediated complement activation pathway in tumor progression and therapy resistance - Lemei Zheng; Jianxia Wei; Mengna Li; Changning Xue; Qingqing Wei; Zubing Wu; Xiaolong Li; Ting Zeng; Huizhen Xin; Wei Xiong; Hongyu Deng; Ming Zhou (Science China Life Sciences, 2026)

Suspensaditerpenes A–Q, anti-inflammatory labdane and nor-labdane diterpenoids from the seeds of Forsythia suspensa - Hui-Ying Li; Meng-Yu Bao; Hao-Ming Xiong; Can-Can Wang; Li-Ping Bai; Wei Zhang; Cheng-Yu Chen; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Model based decision making for efficient drip irrigation strategy of maize in arid northwestern China-A case study in Bayannur district - Yingjian Cao; Ming Zhan; Hang Xiong; Lin Chen; William D. Batchelor; Bowen Yang; Bo Chen; Lijun Li (Field Crops Research, 2026)

Built-in electric field-governed ion sieving in interlayer-engineered TiN–MXene heterostructure anodes for dominant aqueous zinc-ion storage - Inaam Ullah; Ayesha Irfan; Mai Li; Chenxi Li; Samira Saddique; Salamat Ali; Waqar ul Hasan; Muhammad Irfan; Caiyuan Xiong; Jinbo Ming; Qinglin Deng; Chunrui Wang; et al. (Chemical Engineering Journal, 2026)

FT-ICR MS analysis of DOM transformation in steel wastewater zero-liquid discharge systems - Fei Xiong; Hao Yang; Jingbang Yu; Wei Miao; Ce Zhao; Min Tong; Ming Yong; Enchao Li; Zhikao Li (Chemical Engineering Journal, 2026)

Anode interface layers constructed in situ by multifunctional carbon dots for ultra-stable aqueous zinc-ion batteries - Qian-Li Ma; Xi-Rong Zhang; Bao-Juan Wang; Hao-Wen Sun; Huan-Ming Xiong (Chemical Engineering Journal, 2026)

Experimental and numerical investigation of a thermal diode double phase change wall for energy-efficient building envelopes - Yahui Gao; Tingzhen Ming; Hanbing Xiong; Jiyuan Zhou; Xitong Yuan; Wenyu Li; Wenting Lin; Yongjia Wu (Building and Environment, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Amino-modified gangue-derived NaX zeolite for enhanced stabilization of lead and cadmium in contaminated soils: synthesis, performance, and leaching stability - Weiwei Zhu; Jingyi Xiong; Zhuoxi Huangfu; Jiang Yu; Pengxinyue Hang; Cheng Han; Ming Chen; Bin Li; Tao Gao; Junwei Yang; Yao Du (Environmental Geochemistry and Health, 2026)

Benazepril Promotes the Proliferation and Differentiation of Urine-Derived Stem Cells from Children with Nephrotic Syndrome During the Chronic Kidney Disease Stage - Chengqiang Huang; Yuan Yang; Cheng Li; Ling Guo; Ming Liu; Geng Xiong (Biochemical Genetics, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

Methane emissions from global shallow lakes: Patterns, key drivers, and mitigation strategies - Rongwei Xiong; Yong Li; Ming Chen; Jinquan Huang; Yan Xue (Journal of Cleaner Production, 2026)

amh alleles on XY sex chromosomes regulate male differentiation in amphidiploid Carassius auratus - Chun Miao; Meng Lu; Miao Ding; Ming-Tao Wang; Zhi Li; Tian-Zi Yao; Zhi-Xuan Zhu; Wen-Xuan Du; Jun-Sheng Niu; Xiao-Juan Zhang; Shun Li; Peng Yu; et al. (Science China Life Sciences, 2026)

CDGSH Iron Sulfur Domain 1 Relieves Neuronal Ferroptosis via Activating AMPK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

RRBP1 Inhibition Reduces Microglial M1 Polarization and Inflammation-Mediated Neuronal Loss and Oxidative Stress by Regulating ERK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

Solar-driven polypyrrole-decorated polyester filter cotton for efficient desalination and zero liquid discharge - Renpan Xing; Xin Zhong; Jing Wu; Zijun Zhang; Hui Huang; Weizhan Zhong; Ming Li; Weiming Wang; Jun Xiong (Desalination, 2025)

Xuanhong Dingchuan Tang suppresses bronchial asthma inflammation via the microRNA-107-3p/PTGS2/MAPK axis - Xi Ming; Yingzhu Lu; Huihui Huang; Jialin Zheng; Tianzi Wang; Zhuoqun Li; Xingzhu Yu; Lei Xiong (Functional & Integrative Genomics, 2025)

Comparative Transcriptomic Analysis Reveals Molecular Mechanisms Underlying Scale Adhesion Differences Between Carassius auratus indigentiaus and Carassius auratus gibelio - Xin Li; Li-Ming Xiong; Ke-Jun Liu; Hai-Tai Chen; Yi-Ming Xie; Xian-Zhuo Chen; Lei Zhang; Shu-Ting Xiong (Fishes, 2025)
Scale adhesion strength is a key trait in aquaculture, directly influencing disease resistance, survival, and commercial value. The Dongting crucian carp (Carassius auratus indigentiaus, hereafter CaDT) is valued for its rapid growth and superior flesh quality but is characterized by loosely attached scales. In this study, we investigated the morphological and molecular basis underlying scale adhesion by comparing CaDT with the tight-scaled allogynogenetic gibel carp, Zhongke No. 3 (Carassius auratus gibelio, hereafter CaGB). Morphological analysis revealed a significantly lower scale-embedding ratio in CaDT compared to CaGB. To unravel the molecular mechanisms underpinning these phenotypic differences, a comparative transcriptomic analysis was conducted on scale sac, skin, and muscle tissues in CaDT and CaGB. In CaGB, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of differentially expressed genes (DEGs) in the critical scale sac tissue showed a significant upregulation of genes involved in ribosomal pathways. Specifically, key epithelial differentiation markers, including keratin 13 (krt13), keratin 15 (krt15), and metabolic genes, enolase 3-like (eno3l), and phosphoglycerate mutase 2 (pgam2) were significantly down-regulated in CaDT, which suggests a compromised epithelial cell differentiation capacity and reduced energetic and biosynthetic activity. Quantitative PCR (qPCR) validation across three tissues showed high concordance with the RNA-seq results, thereby confirming the reliability of the transcriptomic data. The results offer insight into the molecular basis for understanding scale adhesion traits, and provide valuable insights for selective breeding strategies to improve scale retention in aquaculture species.

Exploring the main and interactive effects of urban morphology on land surface temperature across different functional zones: A local geoshapley analysis based on XAI - Jin-Tao Yang; Xing-Wen Zhou; Xu Chen; Xiong Yao; Mao Li; Ming-Hui Yin; Fei Dong; Shi-Hong Yan; Jia-Liang Zhao (Sustainable Cities and Society, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

A Facile-Synthesized Dual-Network Multi-Ionic Integrated Explosive with Enhanced Detonation Performance and Promoted Aluminum Reactivity - Yun-Fan Yan; Yu Shang; Ming-Yu Guo; Shao-Li Chen; Meng Cui; Zhi-Hong Yu; Wei-Xiong Zhang; Xiao-Ming Chen (Chemical Engineering Journal, 2025)

Frequency adaptability analysis of typical acoustic propagation models - Ming Hui Li; Cheng Chen; Xiao Feng; Chu xiong Wang; Han yue Wang (Frontiers in Marine Science, 2025)
Underwater acoustic propagation is influenced by water column properties, seabed topography, and source frequency, with existing numerical models exhibiting varied performance across different conditions. This study evaluates the frequency adaptability of three acoustic models—BELLHOP (geometric ray-based), RAM (parabolic equation), and KRAKEN (coupled mode)—under diverse seabed topographies, including deep-sea-flat (25–2000 Hz), shallow-sea-flat (25–10000 Hz), and gentle/steep-slope seabed (25–800 Hz). Flat seabed scenarios use the Scooter model as a benchmark, while sloping seabed scenarios are compared against analytical solutions. Results indicate that in a 200 m deep flat ocean environment, BELLHOP achieves high accuracy for frequencies above 200 Hz, KRAKEN performs comparably to RAM below 50 Hz, and RAM excels below 200 Hz. In a 4000 m deep flat ocean, RAM outperforms at frequencies below 100 Hz, while BELLHOP performs well above 100 Hz. For sloping seabed environments with slopes less than 6.5°, RAM demonstrates stability below 100 Hz, while BELLHOP performs better above 100 Hz; for slopes greater than 6.5°, RAM remains stable below 50 Hz, with BELLHOP outperforming above 50 Hz. KRAKEN is found unsuitable for sloping seabed simulations. These findings provide quantitative guidance for selecting acoustic models based on frequency and seabed topography.

Morphology engineering-driven high-performance potassium-based CO2 adsorbents: Interface design and structure-activity relationship study - WeiMing Wang; YuHang Yu; Bo Li; Jun Xiong; GuoQiang Wei; XiXian Yang; Bo Deng; Ming Li; Shuai Peng; Hao Liu (Journal of Environmental Chemical Engineering, 2025)

Moisture-adaptive cellulose/MXene aerogels for synergistic moisture and triboelectric energy harvesting - Jiwei Zhang; Xinran Zhou; Mengjie Wu; Liming Zhu; Zechang Ming; Weikang Li; Yong Xia; Hao Liu; Zijie Zhou; Tao Zhang; Minghui Fan; Jianyong Yu; et al. (Chemical Engineering Journal, 2025)

Moth-inspired isolated venation network nanofiber-based multi-resonant acoustic sensor for enhanced broadband perception - Tianzhe Yang; Yiming Ke; Xiaojuan Ming; Mufang Li; Yanyan Li; Yi Xiong; Weibing Zhong; Dong Wang (Chemical Engineering Journal, 2025)

Soil mesofauna bacterial diversity: Insights from cultured collembolans, enchytraeids, and mites species - Bo-Wen Liu; Jing Wen; Shuai-Fei Ye; Jia-Jia Gu; Ming-Xin Li; Xiao-Bo Xiong; Zong-Zheng Liang; Hong-Tao Wang (Food Webs, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Controlling Effects of Complex Fault Systems on the Oil and Gas System of Buried Hills: A Case Study of Beibuwan Basin, China - Anran Li; Fanghao Xu; Guosheng Xu; Caiwei Fan; Ming Li; Fan Jiang; Xiaojun Xiong; Xichun Zhang; Bing Xie (Journal of Marine Science and Engineering, 2025)
Traps are central to petroleum exploration, where hydrocarbons accumulate during migration. Reservoirs are likewise an essential petroleum system element and serve as the primary medium for hydrocarbon storage. The buried hill is a geological formation highly favorable for reservoir development. However, the factors influencing hydrocarbon accumulation in buried hill reservoirs are highly diverse, especially in areas with complex, active fault systems. Fault systems play a dual role, both in the formation of reservoirs and in the migration of hydrocarbons. Therefore, understanding the impact of complex fault systems helps enhance the exploration success rate of buried hill traps and guide drilling deployment. In the Beibuwan Basin in the South China Sea, buried hill traps are key targets for deep-buried hydrocarbon exploration in this faulted basin. The low level of exploration and research in buried hills globally limits the understanding of hydrocarbon accumulation conditions, thereby hindering large-scale hydrocarbon exploration. By using drilling data, logging data, and seismic data, stress fields and tectonic faults were restored. There are two types of buried hills developed in the Beibuwan Basin, which were formed during the Late Ordovician-Silurian period and Permian-Triassic period, respectively. The tectonic genesis of the Late Ordovician-Silurian period buried hills belongs to magma diapirism activity, while the tectonic genesis of the Permian-Triassic period buried hills belongs to reverse thrust activity. The fault systems formed by two periods of tectonic activity were respectively altered into basement buried hills and limestone buried hills. The negative structural inversion controls the distribution and interior stratigraphic framework of the deformed Carboniferous strata in the limestone buried hill. The faults and derived fractures of the Late Ordovician-Silurian period and Permian-Triassic period promoted the diagenesis and erosion of these buried hills. The faults formed after the Permian-Triassic period are not conducive to calcite cementation, thus facilitating the preservation of the reservoir space formed earlier. The control of hydrocarbon accumulation by the fault system is reflected in two aspects: on the one hand, the early to mid-Eocene extensional faulting activity directly controlled the depositional process of lacustrine source rocks; on the other hand, the Late Eocene-Oligocene, which is closest to the hydrocarbon expulsion period, is the most effective fault activity period for connecting Eocene source rocks and buried hill reservoirs. This study contributes to understanding of the role of complex fault activity in the formation of buried hill traps within hydrocarbon-bearing basins.

Effect of flow rate and dissolved oxygen distribution on aeration of the recirculating aquaculture tank - Zhixin Xiong; Ming Ma; Yu Guo; Yu Sun; Ruoxuan Li (Computers and Electronics in Agriculture, 2025)

Construction of hierarchical nanostructured surface on an organic hybrid selenidostannate with light trapping effect to achieve sunlight-driven environmental remediation - Ji-Ming Yu; Longfei Zhai; Bing Zheng; Haohao Li; Chunhui Hou; Yimin Han; Juan Ma; Zihui Wang; Wei-Wei Xiong (Journal of Hazardous Materials, 2025)

Stage-dependent synergistic impacts of AM fungi and rhizobacteria on phytohormone mediation and field productivity in dryland maize - Muhammad Abrar; Ying Zhu; Wen-Shan Li; Muhammad Aqeel; Umair Ashraf; Muhammad Maqsood Ur Rehman; Jian-Ming Li; Xiao-Fang Gong; Wasim Khan; Wei Wang; You-Cai Xiong (Field Crops Research, 2025)

Enhanced ecological risk of microplastic ingestion by fish due to fragmentation and deposition in heavily sediment-laden river - Lei Du; Baozhu Pan; Xu Han; Dianbao Li; Yueting Meng; Zhiqi Liu; Xiong Xiong; Ming Li (Water Research, 2025)

Numerical simulation of the effect of solar chimneys on NOx-O3 photochemical reaction and ventilation in urban street canyon - Hanbing Xiong; Tianhao Shi; Yongjia Wu; Ruiyue Xia; Xitong Yuan; Renaud de Richter; Wei Li; Yueping Fang; Nan Zhou; Wenyu Li; Chong Peng; Tingzhen Ming (Urban Climate, 2025)

Energy utilization of CO2 thermal management system for electric vehicles in cold climate: Assessment of different heat source modes - Haixu Teng; Ming Li; Jun Wang; Shuangyuan Xiong; Chunhong Lu; Zhanzhuo Song; Haikang Chen; Yan Jiang (International Journal of Refrigeration, 2025)

Temporal and spatial differentiation in the landslide sediment transfer potential in Wenchuan earthquake-impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Jiangang Chen; Tao Yang; Lingfeng Gong; Qingyun Shi; Xianzheng Zhang; Ning Li; Mingwei Li (Landslides, 2025)

DNA damage may cause the reproductive differences between the male tetraploid fish and diploid red crucian carp - Haitao Zhong; Hong Chen; Mingli Liu; Chiye Zhao; Chaoying Luo; Zheduo Xiong; Yan Li; Yilin Wu; Yuheng Wang; Chun Zhang; Chang Wu; Qizhi Liu; et al. (Aquaculture, 2025)

Waste silk-derived photothermal aerogel for efficient interfacial solar desalination - Chao Liang; Yipeng Quan; Wenting Qian; Shuang Guo; Shengjie Zheng; Guangjie Zhang; Mingsong Fan; Jun Xiong; Ming Li (Chemical Engineering Journal, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Polyester fibre sphere solar evaporator for efficient interfacial solar desalination - Yuhang Yu; Chao Liang; Youquan Li; Zijun Zhang; Weiming Wang; Jun Xiong; Ming Li (Journal of Environmental Chemical Engineering, 2025)

Geomorphometric assessment of spatial transfer potential of landslides sediment in seismically impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Lingfeng Gong; Ming Chen; Xianzheng Zhang; Tao Yang; Ning Li; Qingyun Shi; Mingwei Li (Natural Hazards, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Emission factors and driving forces of provincial-level CO2 from electricity production and consumption in China from 2013 to 2020 - Ruoxi Xiong; Chenling Fu; Huimin Chang; Nan Li; Shen Qu; Dong Zhao; Changqing Xu; Jianchuan Qi; Ming Xu (Journal of Environmental Management, 2025)

Highly accurate deformation adaptive pressure sensor integrated with programmatically fabricated strain localizing yarn - Yiming Ke; Weibing Zhong; Xiaojuan Ming; Kaiyue Cui; Shifan Song; Kangyu Jia; Mufang Li; Yi Xiong; Tao Zhao; Dong Wang (Chemical Engineering Journal, 2025)

A robust index was extracted to assess the prolonged changes in debris flow activity after a high magnitude earthquake - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Jiangang Chen; Tao Yang; Lingfeng Gong; Ming Chen; Qingyun Shi; Ning Li (CATENA, 2025)

Warming effects on the emission pathways of N2O and CH4 and the role of water column in shallow eutrophic lakes - Rongwei Xiong; Ming Chen; Yong Li; Guangbao Sun; Jinquan Huang; Yan Xue; Zeyuan Shan; Tianqi Li (Science of The Total Environment, 2025)

An intelligent scheduling model for achieving green automotive outbound logistics - Yan Li; Ming K. Lim; Ming-Lang Tseng; Weiqing Xiong; Yuhe Shi (Journal of Cleaner Production, 2025)

Construction of S-scheme heterojunction based on an organic hybrid silver tin selenide with strong affinity to Cr(VI) for efficient photocatalytic Cr(VI) reduction - Ji-Ming Yu; Chunhui Hou; Wen-Bo Pei; Longfei Zhai; Haohao Li; Yimin Han; Zihui Wang; Juan Ma; Wei-Wei Xiong (Chemical Engineering Journal, 2025)

Dynamic impact of hillslope landslide sediment transfer to ecological environment recovery in earthquake disturbed area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Mingwei Li (Bulletin of Engineering Geology and the Environment, 2025)

Organic matter accumulation driven by land-sea interactions during the Late Cretaceous: A geochemical study of the Nenjiang Formation, Songliao Basin - Congsheng Bian; Shiju Liu; Wei Liu; Xiong Cheng; Xin Liu; Jin Dong; Rui Wang; Yongxin Li; Ming Guan; Qianhui Tian; Wenzhi Zhao (Organic Geochemistry, 2025)

Fast photocatalytic Cr(VI) removal by an organic hybrid silver antimony sulfide coupled with PEDOT - Yimin Han; Longfei Zhai; Wen-Bo Pei; Jiahua Luo; Ji-Ming Yu; Haohao Li; Chunhui Hou; Zihui Wang; Juan Ma; Bing Hu; Wei-Wei Xiong (Journal of Cleaner Production, 2025)

Analytical Solution for Predicting Uplift Bearing Capacity of Branch Pile - Yang Zhou; Ming Song; Yang Liu; Li Xiong; Zhen Chen (Geotechnical and Geological Engineering, 2025)

Hydrogen sulfide alleviates cadmium stress in germinating carrot seeds by promoting the accumulation of proline - Miao Sun; Huan-Xuan Qiao; Tao Yang; Peng Zhao; Jun-Hao Zhao; Jia-Ming Luo; Hai-Ye Luan; Xiang Li; Sheng-Cai Wu; Ai-Sheng Xiong (Journal of Plant Physiology, 2024)

Long-term and multiscale assessment of methanogenesis enhancement mechanisms in magnetite nanoparticle-mediated anaerobic digestion reactor - Jibin Li; Desheng Sun; Siqi Wu; Wenlan Yang; Lei Xiong; Weiming Zhang; Ming Hua; Bingcai Pan (Environmental Research, 2024)

Tree rings-inspired 3D solar evaporator fabricated by rolling polypyrrole decorated waste cotton fabric for efficient desalination - Xin Zhong; Hexiang Lan; Yibing Chen; Youquan Li; Zijun Zhang; Jun Xiong; Linghui Yu; Ming Li (Desalination, 2024)

Exploring the adaptive behaviour and environmental acclimation of artificially-bred Chinese sturgeon (Acipenser sinensis) in semi-open marine environment: insights for endangered species conservation - Huangxin Liu; Pengcheng Li; Xiaoqian Leng; Ming Jiang; Li Shen; Puyuan Wang; Hui Zhang; Jiang Luo; Wei Xiong; Yuan Liu; Hao Du (Reviews in Fish Biology and Fisheries, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Sustainable protein/polysaccharide aerogel for the simultaneous and efficient removal of multiple organic contaminants: Insights from DFT calculations and phenomenological mass–transfer modeling - Ming-Xing Li; Yan-Shu Xiong; Qi-Qi Huang; Yi-Wen Luo; Wei Wei; Hai-Qin Lu; Fang-Xue Hang; Wen Li; Fujie Liu; Kai Li (Journal of Hazardous Materials, 2024)

Differential spatial responses and assembly mechanisms of soil microbial communities across region-scale Taiga ecosystems - Zheng-Xiao Liu; Yue-Ming Lyu; Yang Liu; Yun-Qi Wang; Ming-Min Xiong; Yuan Tang; Xing-Yue Li; Han Sun; Ji-Liang Xu (Journal of Environmental Management, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

Amine-functionalized soy protein/graphene oxide aerogel for efficient removal of multiple sugar-derived contaminants (SDCs): Full life cycle exploration and interaction simulation - Yan-Shu Xiong; Ming-Xing Li; Mei Li; Hai-Qin Lu; Yang Liu; Wei Wei; Yan-Hong Wei; Wen Li; Kai Li (Chemical Engineering Journal, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

CuS and polydopamine-modified polyvinyl alcohol foam for steady interfacial solar desalination of high saltwater - Chenxi Han; Youquan Li; Yibing Chen; Jin Zhang; Zijun Zhang; Yuqiu Ke; Jun Xiong; Linghui Yu; Ming Li (Journal of Environmental Chemical Engineering, 2024)

Dihydroartemisinin regulates the apoptosis and growth of colorectal cancer by suppressing DPYSL2 and increasing TF and ACHE - Xiao Zhang; Jun-Feng Cao; Dunshui Liao; Zengliang Xia; Li Xiong; Mei Wu; Chaochao Wang; Xingyu Yang; Yixin Qiu; Lixin Zhang; Ningbo Chen; Ming Zhang; et al. (Food Bioscience, 2024)

Bio-inspired catalysts for enhanced N₂ electroreduction to NH3: Architecting molecular screening interfaces via active sites microenvironment engineering - Xinyue Chi; Jingxian Li; Xiaoxuan Wang; Yuanyuan Xiong; Shuyuan Li; Kaixin Zhang; Zhenzhen Fu; Jiangzhou Xie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

Study of energy absorption characteristics of coastal ship side structures based on collision accidents - Zhixin Xiong; Ming Ma; Yu Guo; Ruoxuan Li (Ocean Engineering, 2024)

The duality of sulfate-reducing bacteria: Reducing methylmercury production in rhizosphere but enhancing accumulation in rice plants - Pan Guo; Hongxia Du; Qiaozhi Mao; Yuhan Deng; Xun Wang; Jing Li; Bingcai Xiong; Xu Fan; Dingyong Wang; Evgenios Agathokleous; Ming Ma (Journal of Hazardous Materials, 2024)

A crystalline organic hybrid thiogallate containing high content of amino groups for efficient Cr(VI) removal - Ji-Ming Yu; Zhechuan Pan; Jiansheng Wu; Longfei Zhai; Hao Li; Haohao Li; Wei-Wei Xiong (Chemical Engineering Journal, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Multiomics Analyses Explore the Immunometabolic Interplay in the Liver of White Crucian Carp (Carassius cuvieri) After Aeromonas veronii Challenge - Fei Wang; Zi-Rou Zhong; Qing Xie; Jie Ou; Ning-Xia Xiong; Ming-Zhu Huang; Shi-Yun Li; Gang Hu; Zi-Le Qin; Sheng-Wei Luo (Marine Biotechnology, 2024)

Dynamic susceptibility assessment of debris flow hazard after a strong earthquake, Wenchuan County, Sichuan, China - Xianzheng Zhang; Chenxiao Tang; Yongbo Tie; Xiaojuan Li; Chuan Tang; Jiang Xiong; Ming Chen; Lingfeng Gong (Landslides, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Study on the effects of toosendanin against Eimeria tenella and its impact on the apoptosis of cecal cells in chicks - Li’nan Yang; Yanyang Yuan; Lei Xiong; Qingyu Zhao; Ming Yang; Xun Suo; Zhihui Hao (Veterinary Parasitology, 2024)

The hidden threat: Unraveling the impact of microplastics on reproductive health - Mei Wang; Ying Wu; Guigui Li; Yao Xiong; Yuanzhen Zhang; Ming Zhang (Science of The Total Environment, 2024)

Highly salt-resistant polypyrrole decorated waste mop sponge solar evaporator for efficient desalination - Zhihui Yang; Chenxi Han; Yue Zheng; Yibing Chen; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Desalination, 2024)

Identification critical host factors for Japanese encephalitis virus replication via CRISPR screening of human sgRNA library - Le-le Liu; You-qin Yin; Kai-xiong Ma; Jin-chao Xing; Xing-xing Ren; Jin-yu Huang; Ming Liao; Wen-bao Qi; Li-hong Huang (Veterinary Microbiology, 2024)

Preparation of crab-shell-based N, O co-doped graded porous carbon for supercapacitors using the confined nanospace deposition method - Yiming Li; Zhihao Yu; Mengyan Guo; Ming Zhang; Jian Xiong; Yina Qiao; Rui Zhang; Xuebin Lu (Waste Disposal & Sustainable Energy, 2024)

Ferroptosis: a critical mechanism of N6-methyladenosine modification involved in carcinogenesis and tumor progression - Qingqing Wei; Changning Xue; Mengna Li; Jianxia Wei; Lemei Zheng; Shipeng Chen; Yumei Duan; Hongyu Deng; Faqing Tang; Wei Xiong; Ming Zhou (Science China Life Sciences, 2024)

Geochemistry and Zircon U-Pb and Hf Isotopes of Early Devonian Hardawu Granites in the Eastern Segment of the Ultrahigh-Pressure Metamorphic Belt, Northern Qaidam Basin - Hua Li; Ming Wang; Jiqing Li; Haikui Tong; Jiaxiang Dong; Minggang Tian; Xiaolin Chen; Leguang Li; Ting Xie; Xiong Li; Yuying Che (Journal of Earth Science, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Anthracene degradation involved by antibiotic biosynthesis monooxygenase (ABM) in Comamonas testosteroni - Miao Xu; Yonghao Liu; Hui Li; Xiao Yang; Weijie Yue; Yu Zhang; Dong Liu; Ming Wu; Dan Wang; Guangming Xiong; Liquan Guo; Kai Song (International Biodeterioration & Biodegradation, 2024)

Large room-temperature electrocaloric response achieved by tailoring the first-order orthorhombic-tetragonal phase transition in BaTiO3-based ferroelectric ceramics - Ruirui Kang; Wenjing Qiao; Junjie Xiong; Haichao Hu; Ming Wu; Feng Li; Yangfei Gao; Lixue Zhang; Yingying Zhao; Xiaojie Lou (Chemical Engineering Journal, 2024)

Effects of land-use on soil C, N, and P stocks and stoichiometry in coastal wetlands dependent on soil depth and latitude - Jing Xiong; Xuexin Shao; Niu Li; Haijing Yuan; Enjun Liu; Ming Wu (CATENA, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Long Non-Coding RNA MALAT1 Protects Against Spinal Cord Injury via Suppressing microRNA-125b-5p Mediated Microglial M1 Polarization, Neuroinflammation, and Neural Apoptosis - Yuanlong Li; Hua Fan; Xiong Han; Jun Sun; Ming Ni; Xiaodan Hou; Fengqin Fang; Wei Zhang; Peizhi Ma (Molecular Neurobiology, 2024)

Spatio-temporal mapping and long-term evolution of debris flow activity after a high magnitude earthquake - Ming Chen; Chuan Tang; Jiang Xiong; Ming Chang; Ning Li (CATENA, 2024)

Effective value-added strategy of furan compounds with short straight-chain monohydric alcohols based on acid site regulation of zirconium based mesoporous carbon - Jian Xiong; Liying Li; Xuebin Lu; Lei Ye; Zhihao Yu; Wei Li; Ming Zhang; Yiming Li; Jiao Tao; Rui Zhang; Yina Qiao (Biomass and Bioenergy, 2024)

An improved constrained velocity inversion algorithm for geological structures - Jing-Xuan Xiong; Zhen-Hua He; Le Li; Guamg-Ming He; Hong Liu; Lian-Jun Li; Guang-Yin Wang; En-Jia Zhang (Applied Geophysics, 2024)

Ponazuril: Clinical efficacy, ultrastructure, and histopathology studies of in vivo anticoccidial action against Eimeria tenella - Yanyang Yuan; Li’nan Yang; Qingyu Zhao; Lei Xiong; Ming Yang; Xun Suo; Zhihui Hao (Veterinary Parasitology, 2024)

Quasi-closed-loop approach for facile and environmentally friendly red mud reutilization as advanced Li-ion anode material - Dawei Lan; Yixun Gu; Xianglong Chen; Man Mo; Zhijie Fang; Panyu Xiong; Weichi Ye; Gangli Zhao; Tianshi Xiong; Minfeng Huang; Weijian Li; Haiqing Zhan; et al. (Journal of Cleaner Production, 2024)

Porphyrin-Based Two-Dimensional Metal-Organic framework nanosheets for efficient photocatalytic CO2 transformation - Quan Shi; Ming-Hui Chen; Ji Xiong; Ting Li; Ya-Qing Feng; Bao Zhang (Chemical Engineering Journal, 2024)

Innovative no-till seeding technology improves yield and nitrogen use efficiency while reducing environmental pressure in wheat after rice harvesting - Miao Liu; Xiaoli Wu; Ming Li; Tao Xiong; Chaosu Li; Yonglu Tang (Soil and Tillage Research, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Balancing grain yield and environmental performance by optimizing planting patterns of rice-wheat cropping systems - Ming Li; Chaosu Li; Miao Liu; Tao Xiong; Xiaoli Wu; Yonglu Tang (Science of The Total Environment, 2024)

Distribution and migration of heavy metals in the sediment-plant system: Case study of a large-scale constructed wetland for sewage treatment - Rongwei Xiong; Yong Li; Xiufang Gao; Yan Xue; Jinquan Huang; Na Li; Cheng Chen; Ming Chen (Journal of Environmental Management, 2024)

TBK1 upregulates the interferon response against virus by the TBK1-IRF3/7 axis in yellow catfish (Pelteobagrus fulvidraco) - Li-ming Xiong; Lei Zhang; Zhe Long; Xiang Zhao; Yan-rong Ying; Tiao-yi Xiao; Shu-ting Xiong (Fish & Shellfish Immunology, 2024)

The brominated flame retardant tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) as well as hexabromocyclododecane lead to lipid disorders in mice - Xuan-Yue Chen; Yuan-Yuan Li; Lin Lv; Yi-Ming Xiong; Zhan-Fen Qin (Environmental Pollution, 2024)

Effects of BDS flex power on DCB estimation and PPP convergence - Zhou Wu; Shuhui Li; Hongxia Wan; Ming Ji; Pengrui Mao; Shaojie Xiong (GPS Solutions, 2024)

Slope stability calculation based on sparrow search algorithm and Monte Carlo simulation - Li He; Yong-ming Zhao; Bruno Njamba; Yi-he Liu; Hai-tao Xiong (Arabian Journal of Geosciences, 2024)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Paleoproterozoic crustal evolution of the Tarim Craton, NW China: Constraints from geochronology and geochemistry of orthogneisses and granitic veins in the Xingdi region of the Quruqtagh Block - Xiao-Hui Sun; Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hua-Dong Ma; Wei Li; Li-Ming Xiong; Ming-Yi Xia; Chang-Zhi Wu (Precambrian Research, 2023)

Nonlinear effects of socio-economic factors on urban haze in China: Evidence from spatial econometric smooth transition autoregressive regression approach - Huanhuan Xiong; Yaobin Liu; Ming Kuang; Yi Li (Journal of Environmental Management, 2023)

Rational design of p-ZnS@CN with 3D interconnected hierarchical pore structure through pyrolysis of an organic hybrid zinc thiocyanide for electrochemical lithium storage - Longfei Zhai; Ji-Ming Yu; Ting Yang; Haohao Li; Hao Li; Zhechuan Pan; Wei-Wei Xiong (Chemical Engineering Journal, 2023)

Lead dissociation and redistribution properties of actual contaminated farmland soil after long-term EKAPR treatment - Hongyan Ma; Zhengyang Duan; Jianfang Guo; Xuan Zhu; Xiuding Shi; Wenyi Zhou; Ming Jiang; Junfen Xiong; Tianguo Li (Environmental Geochemistry and Health, 2023)

Identification of cadmium phytoavailability in response to cadmium transformation and changes in soil pH and electrical conductivity - Zhuoyi Yan; Wenchuan Ding; Gengxin Xie; Ming Yan; Jianbing Li; Ya Han; Xin Xiong; Chen Wang (Chemosphere, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Carbon nano-onions acting as artificial pili enhance chloramphenicol degradation in an anaerobic membrane bioreactor - Ming-Chao Zhu; Yong-Ze Lu; Shou-Wen Chen; Zhao-Xia Hu; Jing-Wei Wang; Na Li; Raymond Jian-Xiong Zeng (Chemical Engineering Journal, 2023)

Application of remote sensing monitoring to the spatiotemporal variation in debris flow activity in the catastrophic Wenchuan seismic area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Ming Chang; Xianzheng Zhang; Lingfeng Gong; Ning Li; Qingyun Shi; Mingwei Li (CATENA, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Investigation on the flow characteristics near the duct of a pump-jet propulsion under different advance coefficient conditions - Shun Xu; Yong-liang Xiong; Gui-bin Li; Ming-yuan Wei; Xin-ping Long; Bin Ji (Ocean Engineering, 2023)

Fully waste-based solar evaporator in interfacial solar-driven seawater desalination - Yuming Wu; Xin Zhong; Youquan Li; Huan Li; Yongshuang Cai; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Journal of Environmental Chemical Engineering, 2023)

Fe3O4-polyvinyl alcohol sponge as photo-absorber in interfacial solar steam generation - Zhihui Yang; Yuming Wu; Chenxi Han; Yipeng Quan; Youquan Li; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Desalination, 2023)

Perioperative changing patterns and longitudinal trajectories of CA242 with colorectal cancer prognosis: a retrospective longitudinal cohort study - Chunxia Li; Ruimin You; Lizhu Liu; Yanli Li; Hongjiang Pu; Ming Lei; Zhenhui Li; Dingyun You; Qiuxia Xiong; Tao Zhang (Science Bulletin, 2023)

Turnover polypyrrole decorated cotton fabric based solar evaporator for cost-effective and steady desalination - Xin Zhong; Yuming Wu; Pu Zhang; Yibing Chen; Yongshuang Cai; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Journal of Cleaner Production, 2023)

Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Tian-Bing Song; Qian-Li Ma; Xi-Rong Zhang; Jia-Wen Ni; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Drivers of global surface urban heat islands: Surface property, climate background, and 2D/3D urban morphologies - Ledi Shao; Weilin Liao; Peilin Li; Ming Luo; Xuehui Xiong; Xiaoping Liu (Building and Environment, 2023)

Critical Metals Ga, Ge and In in the Global Pb-Zn Deposits: Current Understanding, Challenges and Perspectives - Yi Zheng; Peng-Peng Yu; Zhan-Ke Li; Suo-Fei Xiong; Ling-Li Zhou; Jia-Xi Zhou; Chang-Ming Wang; Yu-Miao Meng; Yu Zhang; Ye-Jian Wang; Jing Xu; Yue Wu; et al. (Journal of Earth Science, 2023)

Paleotopography-constrained numerical modeling of loess landform evolution - Ying Wang; Si-Ming Chen; Li-Yang Xiong; Si-Jin Li (Geomorphology, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Endophytic Phthalate-degrading Bacillus subtilis N-1-gfp colonizing in soil-crop system shifted indigenous bacterial community to remove di-n-butyl phthalate - Li-Hui Liu; Jia-Yan Zhang; Guang-Xuan Tang; Yu-Hong Huang; Xiang-Qing Xie; Jun Geng; Hui-Xiong Lü; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Early 7,8-Dihydroxyflavone Administration Ameliorates Synaptic and Behavioral Deficits in the Young FXS Animal Model by Acting on BDNF-TrkB Pathway - Yu-shan Chen; Si-ming Zhang; Wei Tan; Qiong Zhu; Chao-xiong Yue; Peng Xiang; Jin-quan Li; Zhen Wei; Yan Zeng (Molecular Neurobiology, 2023)

Emission factors and source profiles of volatile organic compounds from typical industrial sources in Guangzhou, China - Chunyan Jiang; Chenglei Pei; Chunlei Cheng; Huizhong Shen; Qianhua Zhang; Xiufeng Lian; Xin Xiong; Wei Gao; Ming Liu; Zixin Wang; Bo Huang; Mei Tang; et al. (Science of The Total Environment, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Ultra-trace detection and efficient adsorption removal of multiple water-soluble volatile organic compounds by fluorescent sensor array - Huachao Che; Shulin Yan; Ming Xiong; Yulun Nie; Xike Tian; Yong Li (Journal of Hazardous Materials, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

Low concentrations of benzophenone-type UV-filters impair testis development in the amphibian Xenopus laevis - Hong-Mei Li; Ying-Chi Zhang; Yuan-Yuan Li; Qing-Qing Zhu; Jie Li; Hai-Ming Xu; Yi-Ming Xiong; Zhan-Fen Qin (Aquatic Toxicology, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Investigation of the 2019 Wenchuan County debris flow disaster suggests nonuniform spatial and temporal post-seismic debris flow evolution patterns - Xianzheng Zhang; Chenxiao Tang; Ning Li; Jiang Xiong; Ming Chen; Mingwei Li; Chuan Tang (Landslides, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Structural variability in the bulk soil, rhizosphere, and root endophyte fungal communities of Themeda japonica plants under different grades of karst rocky desertification - Ming Tang; Jie Liu; Wenpeng Hou; Reed M. Stubbendieck; Han Xiong; Jie Jin; Jiyi Gong; Chen Cheng; Xiaoxin Tang; Yinglong Liu; Zhaofeng Li; Jianfeng Wang; et al. (Plant and Soil, 2022)

Combined game model and investment decision making of power grid-distributed energy system - Yongxiu He; Wei Xiong; Binyou Yang; Hai-yan Yang; Jiu-fang Zhou; Ming-li Cui; Yan Li (Environment, Development and Sustainability, 2022)

Interactive Effects of Cd and Pb on the Photosynthesis Efficiency and Antioxidant Defense System of Capsicum annuum L - Meng Kou; Juan Xiong; Ming Li; Mingxia Wang; Wenfeng Tan (Bulletin of Environmental Contamination and Toxicology, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Effect of increasing rainfall on the thermal—moisture dynamics of permafrost active layer in the central Qinghai—Tibet Plateau - Zhi-xiong Zhou; Feng-xi Zhou; Ming-li Zhang; Bing-bing Lei; Zhao Ma (Journal of Mountain Science, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

Emerging role of metabolic reprogramming in tumor immune evasion and immunotherapy - Chunmei Fan; Shanshan Zhang; Zhaojian Gong; Xiayu Li; Bo Xiang; Hao Deng; Ming Zhou; Guiyuan Li; Yong Li; Wei Xiong; Zhaoyang Zeng; Xiaoling Li (Science China Life Sciences, 2021)

Activity evolution of landslides and debris flows after the Wenchuan earthquake in the Qipan catchment, Southwest China - Qing-yun Shi; Chuan Tang; Ling-feng Gong; Ming Chen; Ning Li; Wei Zhou; Jiang Xiong; Hai Tang; Xiao-di Wang; Ming-wei Li (Journal of Mountain Science, 2021)

An Insight into the Excavation-Induced Stress Paths on Mechanical Response of Weak Interlayer Zone in Underground Cavern Under High Geostress - Shu-Qian Duan; Quan Jiang; Guo-Feng Liu; Jie-Cheng Xiong; Po Gao; Ding-Ping Xu; Ming-Yu Li (Rock Mechanics and Rock Engineering, 2021)

Ferroptosis occurs in phase of reperfusion but not ischemia in rat heart following ischemia or ischemia/reperfusion - Li-Jing Tang; Xiu-Ju Luo; Hua Tu; Heng Chen; Xiao-Ming Xiong; Nian-Sheng Li; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Isolation and complete genome sequencing of the virulent phage vB_EcoS_XY3 infecting multidrug-resistant Escherichia coli - Pan Fu; Qiang Zhao; Li Shi; Qin Xiong; Hongxia Xu; Senmao Cai; Qianqian Xu; Xiaodong Sun; Ming Sang (Archives of Virology, 2021)

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

Effects of arbuscular mycorrhizal fungi on redox homeostasis of rice under Cd stress - Hui Li; Xun Wen Chen; Li Wu; Na Luo; Wei Xiong Huang; Ce Hui Mo; Yan Wen Li; Lei Xiang; Hai Ming Zhao; Quan Ying Cai; Ming Hung Wong (Plant and Soil, 2020)

A novel plant protein-disulfide isomerase participates in resistance response against the TYLCV in tomato - Tong Li; Ya-Hui Wang; Ying Huang; Jie-Xia Liu; Guo-Ming Xing; Sheng Sun; Sen Li; Zhi-Sheng Xu; Ai-Sheng Xiong (Planta, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Selenium accumulation characteristics of Cyphomandra betacea (Solanum betaceum) seedlings - Linjin Lin; Jing Sun; Tonghao Cui; Xiong Zhou; Ming’an Liao; Yunmin Huan; Liu Yang; Caifang Wu; Xianmin Xia; Yuxi Wang; Zhiyu Li; Jinpeng Zhu; et al. (Physiology and Molecular Biology of Plants, 2020)

Phylogenetic patterns of shrub communities along the longitudinal and latitudinal gradients on the northeastern Qinghai–Tibetan Plateau - Yuan-ming Xiao; Lu-cun Yang; Xiu-qing Nie; Chang-bin Li; Feng Xiong; Guo-ying Zhou (Journal of Mountain Science, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Protective effect of isoliquiritigenin against cerebral injury in septic mice via attenuation of NF-κB - Peng Zou; Hong-Ming Ji; Jian-Wei Zhao; Xin-Min Ding; Zi-Gang Zhen; Xuan Zhang; Xiao-Qi Nie; Li-Xiong Xue (Inflammopharmacology, 2019)

Analysis of status and countermeasures of cancer incidence and mortality in China - Chunchun Wu; Mengna Li; Hanbing Meng; Yukun Liu; Weihong Niu; Yao Zhou; Ran Zhao; Yumei Duan; Zhaoyang Zeng; Xiaoling Li; Guiyuan Li; Wei Xiong; et al. (Science China Life Sciences, 2019)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Analysis of albumen gland proteins suggests survival strategies of developing embryos of Pomacea canaliculata - Ya-Ming Xiong; Zhi-Hui Yan; Jia-En Zhang; Hai-Yun Li (Molluscan Research, 2018)

Analysis of future drought characteristics in China using the regional climate model CCLM - Jinlong Huang; Jianqing Zhai; Tong Jiang; Yanjun Wang; Xiucang Li; Run Wang; Ming Xiong; Buda Su; Thomas Fischer (Climate Dynamics, 2018)

Trend analysis of cancer incidence and mortality in China - Fang Wei; Yingfen Wu; Le Tang; Fang Xiong; Can Guo; Xiayu Li; Ming Zhou; Bo Xiang; Xiaoling Li; Guiyuan Li; Wei Xiong; Zhaoyang Zeng (Science China Life Sciences, 2017)

Evaluation of European Schizophrenia GWAS Loci in Asian Populations via Comprehensive Meta-Analyses - Xiao Xiao; Xiong-jian Luo; Hong Chang; Zichao Liu; Ming Li (Molecular Neurobiology, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Selective and Competitive Adsorption of Azo Dyes on the Metal–Organic Framework ZIF-67 - Zhan-hang Zhang; Jing-li Zhang; Jian-ming Liu; Zhen-hu Xiong; Xu Chen (Water, Air, & Soil Pollution, 2016)

Identification and molecular characterization of one novel 1SPl-encoded s-type low molecular weight glutenin B-subunit from 1Sl(1B) substitution line of wheat variety Chinese Spring (Triticum aestivum) - Xiong Deng; Shun-li Wang; Shou-min Zhen; Wen-ying Zhang; Yue-ming Yan (Biologia, 2016)

MAOA Variants and Genetic Susceptibility to Major Psychiatric Disorders - Zichao Liu; Liang Huang; Xiong-jian Luo; Lichuan Wu; Ming Li (Molecular Neurobiology, 2016)

Rutaecarpine attenuates hypoxia-induced right ventricular remodeling in rats - Wen-Qun Li; Xiao-Hui Li; Jie Du; Wang Zhang; Dai Li; Xiao-Ming Xiong; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Adaptive evolution of interleukin-3 (IL3), a gene associated with brain volume variation in general human populations - Ming Li; Liang Huang; Kaiqin Li; Yongxia Huo; Chunhui Chen; Jinkai Wang; Jiewei Liu; Zhenwu Luo; Chuansheng Chen; Qi Dong; Yong-gang Yao; Bing Su; et al. (Human Genetics, 2016)

Petrology, geochemistry, and geochronology of mafic rocks from the Taoxinghu Devonian ophiolite, LongmuCo–Shuanghu–Lancang suture zone, northern Tibet: evidence for an intra-oceanic arc–basin system - Yan-Wang Wu; Cai Li; Meng-Jing Xu; Chao-Ming Xie; Ming Wang; Sheng-Qing Xiong; Zheng-Guo Fan (International Geology Review, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Integrating ChIP-sequencing and digital gene expression profiling to identify BRD7 downstream genes and construct their regulating network - Ke Xu; Wei Xiong; Ming Zhou; Heran Wang; Jing Yang; Xiayu Li; Pan Chen; Qianjin Liao; Hao Deng; Xiaoling Li; Guiyuan Li; Zhaoyang Zeng (Molecular and Cellular Biochemistry, 2016)

Dehydroandrographolide enhances innate immunity of intestinal tract through up-regulation the expression of hBD-2 - Wen-Bi Xiong; Zhen-Jun Shao; Yao Xiong; Jian Chen; Yun Sun; Ling Zhu; Li-Ming Zhou (DARU Journal of Pharmaceutical Sciences, 2015)
Background Dehydroandrographolide (DA) is one of major active components in the well-known oriental herbal medicine Andrographis paniculata (Burm.f) Nees which belongs to the Acanthaceae family. DA is used for the treatment of infections in China. However, DA has not been found to significantly inhibit bacterial and viral growth directly. The current study investigates the effect of DA on the expression of human β –defensin-2 (hBD-2) in human intestinal epithelial cells and the possible signaling pathways. Methods Human intestinal epithelial HCT-116 cells were incubated with 1–100 μM DA for 2–24 h. RT–PCR and Western blot were used to assess the expression of hBD-2. The specific inhibitors were used and the levels of phosphorylation of signaling molecules were detected for dissecting the signaling pathways leading to the induction of hBD-2. Results MTT assay showed there was no obvious cytotoxicity for HCT-116 cells by 1–100 μM DA treatment. RT-PCR and Western blot assays showed that DA (1–100 μM) could up-regulate the expression of hBD-2, and the effect lasted longer than 24 h. By using SB203580 and SB202190 (inhibitors of p38), the enhancement of hBD-2 expression were significantly attenuated. However, inhibitor of ERK and inhibitor of JNK could not block the effect of DA. Furthermore, Western blot found activation of p38 but not ERK and JNK in DA-treated HCT-116 cells. Conclusion The results suggested that DA enhanced innate immunity of intestinal tract by up-regulating the expression of hBD-2 through the p38 MAPK pathways.

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Identification of volatile and softening-related genes using digital gene expression profiles in melting peach - Xiong-wei Li; Jun Jiang; Li-ping Zhang; Yi Yu; Zheng-wen Ye; Xiu-min Wang; Jing-yi Zhou; Ming-liang Chai; Hui-qin Zhang; Pere Arús; Hui-juan Jia; Zhong-shan Gao (Tree Genetics & Genomes, 2015)

Nicotine Inhibits Microglial Proliferation and Is Neuroprotective in Global Ischemia Rats - Yan-Zhong Guan; Xiu-Dong Jin; Li-Xin Guan; Hua-Cheng Yan; Pu Wang; Zhi Gong; Shu-Ji Li; Xiong Cao; Yan-Li Xing; Tian-Ming Gao (Molecular Neurobiology, 2015)

Transcriptome-wide identification of the genes responding to replanting disease in Rehmannia glutinosa L. roots - Yan Hui Yang; Ming Jie Li; Xin Yu Li; Xin Jian Chen; Wen Xiong Lin; Zhong Yi Zhang (Molecular Biology Reports, 2015)

Pitavastatin calcium improves endothelial function and delays the progress of atherosclerosis in patients with hypercholesterolemia - Jing Zhao; Hui-min Yan; Ya Li; Jia Wang; Lu Han; Zhi-hao Wang; Meng-xiong Tang; Wei Zhang; Yun Zhang; Ming Zhong (Journal of Zhejiang University-SCIENCE B, 2015)

Systemic nematicidal activity and biocontrol efficacy of Bacillus firmus against the root-knot nematode Meloidogyne incognita - Jing Xiong; Qiaoni Zhou; Haiyan Luo; Liqiu Xia; Lin Li; Ming Sun; Ziquan Yu (World Journal of Microbiology and Biotechnology, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

CCAAT-enhancer binding protein (C/EBP) β regulates insulin-like growth factor (IGF) 1 expression in porcine liver during prenatal and postnatal development - Yiting Tang; Kai Xiong; Ming Shen; Yulian Mu; Kui Li; Honglin Liu (Molecular and Cellular Biochemistry, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Transcript and metabolite alterations increase ganoderic acid content in Ganoderma lucidum using acetic acid as an inducer - Ang Ren; Xiong-Biao Li; Zhi-Gang Miao; Liang Shi; Ai-Liang Jaing; Ming-Wen Zhao (Biotechnology Letters, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Electroacupuncture Attenuates Reference Memory Impairment Associated with Astrocytic NDRG2 Suppression in APP/PS1 Transgenic Mice - Feng Wang; Haixing Zhong; Xuying Li; Ye Peng; Renee Kinden; Wei Liang; Xin Li; Ming Shi; Lixin Liu; Qiang Wang; Lize Xiong (Molecular Neurobiology, 2014)

Detection of polyketide synthase and nonribosomal peptide synthetase biosynthetic genes from antimicrobial coral-associated actinomycetes - Jie Li; Jun-De Dong; Jian Yang; Xiong-Ming Luo; Si Zhang (Antonie van Leeuwenhoek, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Historical trend of nitrogen and phosphorus loads from the upper Yangtze River basin and their responses to the Three Gorges Dam - Chengchun Sun; Zhenyao Shen; Ruimin Liu; Ming Xiong; Fangbing Ma; Ouyang Zhang; Yangyang Li; Lei Chen (Environmental Science and Pollution Research, 2013)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Cell death in intervertebral disc degeneration - Fan Ding; Zeng-wu Shao; Li-ming Xiong (Apoptosis, 2013)

Construction and analysis of different expression cDNA libraries in Rehmannia glutinosa plants subjected to continuous cropping - Yan Hui Yang; Zhong Yi Zhang; Hua Min Fan; Yi Dan Zhao; Ming Jie Li; Juan Li; Jun Ying Chen; Wen Xiong Lin; Xin Jian Chen (Acta Physiologiae Plantarum, 2013)

An L-Type Calcium Channel Agonist, Bay K8644, Extends the Window of Intervention Against Ischemic Neuronal Injury - Hong-hai Hu; Shu-ji Li; Pu Wang; Hua-cheng Yan; Xiong Cao; Feng-qin Hou; Ying-ying Fang; Xin-hong Zhu; Tian-ming Gao (Molecular Neurobiology, 2013)

Long non-coding RNAs in cancer - ZhaoJian Gong; ShanShan Zhang; WenLing Zhang; HongBin Huang; Qiao Li; Hao Deng; Jian Ma; Ming Zhou; JuanJuan Xiang; MingHua Wu; XiaYu Li; Wei Xiong; et al. (Science China Life Sciences, 2012)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Dynamic sieving capillary electrophoresis analysis of xylitol selenite-induced apoptosis in SMMC-7221 cells - Ming Lei; Didi Chen; Xiaojie Deng; Jing Liu; Layue Chen; Yanli Liu; Bing Li; Hancao Yao; Guomei Xiong; Yu Cao; Jihong Yang; Chao Qi (Biotechnology Letters, 2012)

Partial Purification and Characterization of Fibrinolytic Enzymes from Yellow Mealworm - Ming Xing Huang; Yun Ye; Ya Xiong Chen; Ya Li Han (International Journal of Peptide Research and Therapeutics, 2012)

Role of mitochondrial pathway in compression-induced apoptosis of nucleus pulposus cells - Fan Ding; Zeng-Wu Shao; Shu-Hua Yang; Qiang Wu; Fei Gao; Li-Ming Xiong (Apoptosis, 2012)

The Role of Para-Aortic Lymphadenectomy in Surgical Management of Patients with Stage N+ Rectal Cancer Below the Peritoneal Reflection - Yan-Long Liu; Yi-Hui Wang; Yan-Mei Yang; Ming-Qi Li; Shi-Xiong Jiang; Xi-Shan Wang (Cell Biochemistry and Biophysics, 2012)

Nasopharyngeal carcinoma: Advances in genomics and molecular genetics - ZhaoYang Zeng; HongBin Huang; WenLing Zhang; Bo Xiang; Ming Zhou; YanHong Zhou; Jian Ma; Mei Yi; XiaYu Li; XiaoLing Li; Wei Xiong; GuiYuan Li (Science China Life Sciences, 2011)

Comparison of cardioprotective and anti-inflammatory effects of ischemia pre- and postconditioning in rats with myocardial ischemia–reperfusion injury - Jun Xiong; Qiang Wang; Fu-Shan Xue; Yuan-Jing Yuan; Shan Li; Jian-Hua Liu; Xu Liao; Yan-Ming Zhang (Inflammation Research, 2011)

Stress responsive gene CIPK14 is involved in phytochrome A-mediated far-red light inhibition of greening in Arabidopsis - YuZhi Qin; Ming Guo; Xu Li; XingYao Xiong; ChangZheng He; XianZhou Nie; XuanMing Liu (Science China Life Sciences, 2010)

Differentially Expressed Outer Membrane Proteins of Vibrio alginolyticus in Response to Six Types of Antibiotics - Xiao-Peng Xiong; Chao Wang; Ming-Zhi Ye; Tian-Ci Yang; Xuan-Xian Peng; Hui Li (Marine Biotechnology, 2010)

Mapping the interaction site of prion protein and Sho - Wan Jiayu; Hao Zhu; Xu Ming; Wang Xiong; Wu Songbo; Song Bocui; Liu Wensen; Li Jiping; Meng Keying; Li Zhongyi; Gao Hongwei (Molecular Biology Reports, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

A rapid method for detection of PrP by surface plasmon resonance (SPR) - Wan Jiayu; Wang Xiong; Li Jiping; Liu Wensen; Xu Ming; Liu Linna; Xu Jing; Wang Haiying; Gao Hongwei (Archives of Virology, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Environmental preferences of longlining for yellowfin tuna ( Thunnus albacares ) in the tropical high seas of the Indian Ocean - LI MING SONG; YU ZHANG; LIU XIONG XU; WEN XIN JIANG; JIA QIAO WANG (Fisheries Oceanography, 2008)
A survey of yellowfin tuna, Thunnus albacares , fishing ground was carried out on board of the Chinese longliners from September 15 to December 12, 2005 in the tropical high seas of the Indian Ocean. The depth at which each yellowfin tuna was hooked was estimated using a stepwise regression analysis of theoretical hook depth and observed average hook depth measured using a temperature depth recorder. Water temperature, salinity, chlorophyll a , dissolved oxygen and thermocline, which are important variables influencing yellowfin tuna habitats, were measured in the survey. Catch rates of yellowfin tuna were then analyzed with respect to depth, temperature, salinity, chlorophyll a , dissolved oxygen and thermocline. We suggest that the optimum ranges of swimming depth, water temperature, chlorophyll a and dissolved oxygen concentration for yellowfin tuna are 100.0–179.9 m, 15.0–17.9°C, 0.090–0.099 μ g L −1 , 2.50–2.99 mg L −1 , respectively; that salinity has less influence on the vertical distribution of adult yellowfin tuna; and that yellowfin tuna are mainly distributed within the thermocline in the high seas of the Indian Ocean. Our results match the yellowfin tuna’s vulnerability to deep longline fishing gear well.

Malassezia Folliculitis in China - Glenn S. Bulmer; Xiong Ming Pu; Li Xia Ti Yi (Mycopathologia, 2008)

Identification of functional candidate genes for drought tolerance in rice - Bin-Ying Fu; Jian-Hua Xiong; Ling-Hua Zhu; Xiu-Qin Zhao; Hua-Xue Xu; Yong-Ming Gao; Yang-Sheng Li; Jian-Long Xu; Zhi-Kang Li (Molecular Genetics and Genomics, 2007)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Formation of archegonium chamber is associated with nucellar-cell programmed cell death in Ginkgo biloba - Da-Hui Li; Xiong Yang; Ke-Ming Cui (Protoplasma, 2007)

Preoperative localization and minimally invasive management of primary hyperparathyroidism concomitant with thyroid disease - Yi-xiong Zheng; Shao-ming Xu; Ping Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Outbreak of Trichophyton verrucosum in China Transmitted from Cows to Humans - Pu Xiong Ming; Yi Li Xia Ti; Glenn S. Bulmer (Mycopathologia, 2006)

Codon-modifications and an endoplasmic reticulum-targeting sequence additively enhance expression of an Aspergillus phytase gene in transgenic canola - Ri-He Peng; Quan-Hong Yao; Ai-Sheng Xiong; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2006)

Vitreoscilla hemoglobin overexpression increases submergence tolerance in cabbage - Xian Li; Ri-He Peng; Hui-Qin Fan; Ai-Sheng Xiong; Quan-Hong Yao; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2005)